Analysis on drug combinations for bacteria causing skin infections - Win, Mar Soe. (2010)
Methicillin Resistant Staphylococcus aureus (MRSA) is the one of the most common bacteria that causes skin infections. MRSA has been emerging as important threat to the health of the society as it has developed resistance to more newly synthesized antibiotics. This study emphasize on the combination of western and eastern drugs to combat the problem of MRSA resistance. Four Western drugs and four eastern drugs are used in this study which forms a matrix to give 16 combinations. Checkerboard method for broth microdilution is adopted in the drug interaction studies and time killing curves were done for the interactions which show significant interactions. Ths study can conclude that Eastern Drugs can be very good candidates for the combination therapy for treatment of MRSA skin infections.